Gainline Africa : a case study of sport-for-development organizations and the role of organizational relationship building via social media - Hambrick, Marion E.; Svensson, Per G. (London : Human Kinetics, Inc., 2015)
Sport organizations can use social media to build relationships with current and potential stakeholders. These opportunities are pertinent for smaller niche and sport-for-development-and-peace (SDP) organizations, which rarely receive the same media and consumer attention as their larger, more mainstream counterparts. This study examined the role of social media with 1 SDP organization and used qualitative data collection and analysis to explore what social-media platforms the staff members selected, how they used these platforms, and what benefits and challenges they faced with this use. Their identified social-media activities were 3-fold: disseminating news, promoting events, and educating stakeholders. Some hurdles arose with this use, in particular attempting to engage readers in conversations and ensuring that the posted messages uniformly relayed organizational goals. SDP and other organizations can use social media to achieve communication objectives but should recognize the potential challenges associated with these efforts.
Originally published in Hambrick, M. E., & Svensson, P. G. (2015). Gainline Africa: A case study of sport-for-development organizations and the role of organizational relationship building via social media. International Journal of Sport Communication, 8(2), 233-254. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sports administration; Social media; Sports management